Penerapan Reliability Centered Maintenance (RCM) Untuk Perawatan Mesin Twin Screw Extruder - Sofian Bastuti; Rini Alfatiyah; Riki Effendi (Universitas Muhammadiyah Semarang, 2021)
The industrial sector is currently increasingly competitive and intensively developed through increasingly sophisticated technology. One of the factors supporting the effectiveness and efficiency of production is the engine, so that engine performance needs to be maximized. PT. Nirwana Internar Jaya is a company engaged in the manufacture of pipes using a twin screw extruder machine. The machine does production continuously, so it does not rule out the possibility of downtime. This study aims to determine the optimal maintenance action and determine the maintenance time interval on the twin screw extruder machine using the Reliability Centered Maintenance (RCM) method. The results obtained are that it can reduce the downtime of the twin screw extruder machine from 72.5 hours to 27.5 hours by performing maintenance on heating control system components with maintenance time intervals of 155.15 hours or 7 days, motor cooling fan 739.02 hours or 31 days and blower/fan components with maintenance intervals of 828.08 hours or 35 days. Condition monitoring measures also need to be taken to reduce disturbances that can hinder production activities.